SISPA UTHM Online Logistic Management System - Norhaimi, Norhafizah Azmi; Mohd Nawi , Nazri (Applied Information Technology And Computer Science, 2022)
Online Logistics Management System is a system developed to facilitate the work of logistics goods management at SISPA UTHM (Siswa Siswi Pertahanan Awam Universiti Tun Hussein Onn Malaysia). Previously, logistics management was still done manually by filling in the number information or loan in the form. This method is inefficient due to the easy loss of records due to excessive paper usage and human negligence. In addition, the process of retrieving forms or borrower information becomes difficult due to the large number of forms and needs to be done one by one to ensure that they are not exchanged with other forms. By looking at these weaknesses, the Online Logistics Management System was developed to assist the management of forms which is more efficient and effective on behalf of the SISPA office as well as to reduce the use of paper to manage the logistics process. The system was developed using Dreamweaver, XAMPP and phpMyAdmin software, encoding HTML, PHP and using the Agile development model methodology. This system allows users to view the list of logistics items and fill out the application form in the system easily. The system also makes it easy for administrators to update lists, review and validate application forms, and generate reports.